ANALYSIS OF THE DEVELOPMENT OF VIRTUAL FAN COMMUNITIES MEDIA SPACES - A. N. Timokhovich; O. I. Nikuradze (Вестник университета)
The article deals with the development of media spaces of virtual fan communities. The aim of the research was to reveal the specifics of online communication of virtual fan communities with the audience. The paper investigates the dialectics of the concepts of fan-community, media space, fandom. The article considers the main approaches to studying media space by Russian and foreign authors. The study describes the traditional offline communication practices of the fandoms. The authors substantiate the problem of the existence of a variety of communication channels of the fan communities with the audience (negative interpretation of content, limitations in monetization and evaluation of the effectiveness of communication practices, the growth of costs for the diversification of content, taking into account the features of different platforms). The paper identifies the trend of centralization of fan communities and the possibilities of technological support of user experience at all stages of the communication process as part of the use of online platform. The article gives an analysis of the media environment and media spaces of South Korea’s fan communities on the example of the South Korean case of the development of the fandom media space in the format of the Weverse mobile application. The study considers the techniques of interaction with the audience in the offline interaction limitations. The authors formulate conclusions about the specifics of the extended functionality of the platform, about the provided ways of organizing the virtual fan media space with the help of the platform; about the coming trend of transferring fan activities into the virtual environment.